Compact sext‐band bandpass filter based on single multimode resonator with high band‐to‐band isolations. Issue 9 (4th April 2016) - Ai, Jing; Zhang, Yonghong; Xu, Kai Da; Guo, Yingjiang; Joines, William Thomas; Liu, Qing Huo
Abstract : On the basis of a single multimode resonator (MMR), a miniaturised microstrip sext‐band bandpass filter (BPF) with high band‐to‐band isolations has been presented. The proposed MMR is an stepped impedance resonator (SIR) with one short‐circuited stub loaded in the middle and two identical open‐circuited stubs located at two sides. Transmission poles (TPs) and transmission zeros (TZs) can be excited when the electrical lengths of two open stubs increase. The TZs introduced by open stubs separate the TPs into multiple groups; therefore, the design of a sext‐band BPF becomes available. Moreover, two input/output tapped branches and radical stub‐loaded short‐circuited lines are treated as perturbation structures in order to increase design freedoms for improving filter performance. Good agreement between simulated and measured results validates the design method.